WORKSHOP FOTOGRAFI PRODUK UNTUK MENINGKATKAN MINAT BERWIRAUSAHA SISWA SMA MUHAMMADIYAH JAYAPURA: (Product Photography Workshop to Enhance Students’ Entrepreneurial Interest at Muhammadiyah Jayapura Senior High School) - Dani Arisandi DN; Wahyu Kumala Sari (JBMP: Jurnal Bhakti Muhammadiyah Papua, 2026)
This community engagement program aims to enhance the understanding and skills of students at SMA Muhammadiyah Jayapura in product photography as foundational competencies to support entrepreneurial interest in the digital era. Product photography plays a crucial role in modern marketing because it significantly influences perceived quality, visual appeal, and consumer purchasing decisions. The training was conducted through three main stages: planning, implementation, and evaluation. The instructional methods included lectures, interactive discussions, and hands-on practice using smartphone-based photography techniques. The results indicate a high level of enthusiasm among participants, demonstrated through active involvement in discussions and strong engagement during practical sessions. Students successfully developed their understanding of lighting, composition, multi-angle product shooting techniques, as well as the use of smartphone camera features and basic editing applications. Based on the evaluation, the program effectively stimulated students’ visual creativity and improved their practical skills in product photography. It is recommended that similar activities be continued through follow-up mentoring and integration into school entrepreneurship programs.